Climate Change Synchronizes Growth and iWUE Across Species in a Temperate-Submediterranean Mixed Oak Forest - Dorado-Liñán, Isabel; Valbuena-Carabaña, María; Cañellas, Isabel; Gil, Luis; Gea-Izquierdo, Guillermo (Frontiers in Plant Science, 2020)
Tree species have good tolerance to a range of environmental conditions, though their ability to respond and persist to environmental changes is dramatically reduced at the rear-edge distribution limits. At those edges, gene flow conferring adaptation is impaired due to lack of populations at lower latitudes. Thus, trees mainly rely on phenotypic changes to buffer against long-term environmental changes. Interspecific hybridization may offer an alternative mechanism in the generation of novel genetic recombinants that could be particularly valuable to ensure persistence in geographically isolated forests. In this paper, we take advantage of the longevity of a temperate-submediterranean mixed-oak forest to explore the long-term impact of environmental changes on two different oak species and their hybrid. Individual trees were genetically characterized and classified into three groups: pure Quercus petraea (Matt.), Liebl, pure Q. pyrenaica Willd, and hybrids. We calculated basal area increment and intrinsic water-use efficiency (iWUE) from tree-ring width and δ13C per genetic group, respectively. Tree-growth drivers were assessed using correlation analyses and generalized linear mixed models for two contrasting climatic periods: (1880–1915, colder with [CO2] < 303 ppm; and 1980–2015, warmer with [CO2] > 338 ppm). The three genetic groups have increased radial growth and iWUE during the last decades, being the least drought-tolerant QuPe the most sensitive species to water stress. However, no significant differences were found among genetic groups neither in mean growth rate nor in mean iWUE. Furthermore, little differences were found in the response to climate among groups. Genetic groups only differed in the relationship between δ13C and temperature and precipitation during the earlier period, but such a difference disappeared during the recent decades. Climate change may have promoted species-level convergence as a response to environment-induced growth limitations, which translated in synchronized growth and response to climate as well as a tighter stomatal control and increased iWUE across coexisting oak species.